1999
DOI: 10.1021/jp9908451
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Effect of NiCo, Ni and Co Catalysts on the Yield of Single-Wall Carbon Nanotubes Formed by Pulsed Nd:YAG Laser Ablation

Abstract: We revealed that the yield of SWNTs formed by Nd:YAG laser ablation depends on the target composition with yields following the order C x Ni y Co y > C x Ni y ≫ C x Co z . The SWNT bundles in the web formed when using the C x Ni y Co y target (web-C x Ni y Co y ) is thicker and longer than those in the web-C x Ni y . The diameters of the SWNTs in the web-C x Ni y Co y were larger and more uniform than those of the SWNTs in the web-C x Ni y . The NiCo particles in the web-C x Ni y Co y and the Ni particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(67 citation statements)
references
References 19 publications
0
67
0
Order By: Relevance
“…The first and most applicable catalysts are Ni, Fe and Co and their 1:1 mixture [98]. It is worth noticing that bimetallic catalysts are more productive [100]. Application of other catalytic particles, for example, platinum, sulfur, molybdenum or yttrium, did not demonstrate high-yield or high-quality CNT formation.…”
Section: Laser Ablationmentioning
confidence: 99%
“…The first and most applicable catalysts are Ni, Fe and Co and their 1:1 mixture [98]. It is worth noticing that bimetallic catalysts are more productive [100]. Application of other catalytic particles, for example, platinum, sulfur, molybdenum or yttrium, did not demonstrate high-yield or high-quality CNT formation.…”
Section: Laser Ablationmentioning
confidence: 99%
“…The latter also catalyzes carbon feedstock creation from incoming CO molecules. Later observations by Yudasaka et al, who employed laser evaporation experiments with several laser target materials [15], indicated that the metal particles are in fact molten carbide droplets, which segregate carbon during cooling. At the same time it became commonplace in the catalytic chemical vapor decomposition (CCVD) community to discriminate between "root (or base) growth" [23,37], in which the metal particles remain on a substrate, and "tip growth" [23], in which the metal particle is not anchored on the substrate surface.…”
Section: Early Hypotheses On the Role Of The Metal Catalyst During Swmentioning
confidence: 99%
“…For SWNT growth on nm-size particles of Au, Ag, and Ni, Takagi et al demonstrated that the size of the catalyst particles plays a crucial role in determining their catalytic activity [13]. Since the earliest days of SWNT research, the metal catalysts were believed to play essential roles in the nucleation and continued growth processes of SWNTs at high temperature [9,14,15]. Metal-free SWNT growth has not been achieved until rather recently [16 19], with earlier efforts in this direction presumably being discouraged by the observation that noncatalytic carbon-arc synthetic routes had led only to multiwalled carbon nanotubes (MWNTs) [20], which are assumed to crystallize in supercooled liquid carbon droplets [11].…”
Section: Introductionmentioning
confidence: 99%
“…laser fluence and wavelength, pulse duration, carrier gas type, pressure, and flow rate [15][16][17][18]. Experiments such as light scattering and photoluminescence have been used for real-time imaging of the particle production process to study the effects of different experimental parameters [5,19,20].…”
Section: Introductionmentioning
confidence: 99%